Рассказы: рассказы : перевод с английского / Р. Киплинг - Киплинг Редьярд (Бимпа, 1991)
Экземпляры: ф. 9 (20211122) / Инвентарный номер: 30970 / Цена: 10.00 / Авт.знак: К 42 / ГРНТИ: 17.82 / ББК: 84(4Вел)